KEBIJAKAN SISTEM PEMASYARAKATAN DALAM UPAYA PENANGGULANGAN KEPADATAN (OVERCROWDED) PENGHUNI LEMBAGA PEMASYARAKATAN - Elizabeth Ghozali; Pandapotan Tamba (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Overcrowding in correctional institutions occurs in a complex manner between the system and implementation in the field with all its limitations. Therefore, it is necessary to study the causes of overcrowded prisons in terms of criminal policy in Indonesia and strategies for dealing with overcrowded prisons in Indonesia. By using normative legal research methods and supported by empirical legal research methods, it is concluded that the factors causing overcrowded prisons include Indonesian criminal policy which is still oriented towards imprisonment, excessive pre-trial detention and the mindset of law enforcers in Indonesia who like to choose prison punishment efforts rather than other efforts. The comprehensive and multi-party strategies and steps for handling overcrowded prisons in Indonesia can be carried out through efforts, including: changing the orientation/reform of criminal law politics and the criminal justice system, by implementing a policy of decriminalization of acts that are not criminal acts, forming and developing non-prison sanctions policies (alternatives of imprisonment), restorative justice, and forming procedural laws that are able to stop excessive detention.Keywords: Overcrowded, Correctional Institutions.